2017
DOI: 10.1037/xlm0000302
|View full text |Cite
|
Sign up to set email alerts
|

The role of long-term memory in a test of visual working memory: Proactive facilitation but no proactive interference.

Abstract: We report four experiments examining whether associations in visual working memory are subject to proactive interference from long term memory (LTM). Following a long-term learning phase in which participants learned the colors of 120 unique objects, a working memory (WM) test was administered in which participants recalled the precise colors of three concrete objects in an array. Each array in the WM test consisted of one old (previously learned) object with a new color (old-mismatch), one old object with its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
83
4
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(107 citation statements)
references
References 71 publications
(108 reference statements)
10
83
4
2
Order By: Relevance
“…Alternatively, the PI effect may be better interpreted as a decision-making phenomenon that occurs during retrieval. Oberauer, Awh, and Sutterer (2017) proposed that responses to the probe involve a competition between a familiarity signal from LTM and the available content of WM. Familiarity with the probe can be used to make a decision, which is beneficial on positive trials but detrimental on RP trials.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the PI effect may be better interpreted as a decision-making phenomenon that occurs during retrieval. Oberauer, Awh, and Sutterer (2017) proposed that responses to the probe involve a competition between a familiarity signal from LTM and the available content of WM. Familiarity with the probe can be used to make a decision, which is beneficial on positive trials but detrimental on RP trials.…”
Section: Discussionmentioning
confidence: 99%
“…For the WM system to work effectively, it has to retrieve information from long-term memory selectively, so that only information useful for the current task enters WM (Oberauer, 2009). A demonstration of the effectiveness of this gating mechanism comes from experiments investigating the effect of previously acquired long-term memories on WM performance (Oberauer, Awh, & Sutterer, 2017). We had participants learn 120 associations between everyday objects and randomly selected colors.…”
Section: Attention As Selectionmentioning
confidence: 99%
“…Our knowledge of the external world is always based on the long-term memories we experienced previously. Human studies have shown the benefits of long-term memory for learning new information with similar principle (Gerven et al, 2017;Oberauer et al, 2017;Wang et al, 2017). In addition, rule-based learning (combined cues with an abstract principle) has been reported during associative learning both in human and animal studies (Racht-Delatour and Massioui, 1999;Wills et al, 2011;Maes et al, 2017;Broschard et al, 2019).…”
Section: Introductionmentioning
confidence: 99%